MODEL TATA KELOLA PEDAGANG KAKI LIMA (PKL) DI KOTA JAMBI - Tona Aurora Lubis; Erwita .; Raja Sarah (Jurnal Dinamika Manajemen, 2014)
The purpose of this research is to reveal the  governance of street vendors, based on the street vendors’ profiles namely finance, marketing, human resource and operational management in Jambi City. Those indicators will later be formulated to be a comprehensif model of street vendors governance. This research used mixed method, firstly used sequential exploratory designthen qualitative and quantitative method. In qualitative method, this research uses Interpretive Phenomenology, and Partial Least Square (PLS) for the quantitative method. The result of this research shows that the finance, marketing and human resource management have effect on street vendors governance, however, operational management has no effect.Keywords:    street vendors, governance, finance, marketing, human resource, operational